Power Allocation Schemes for DAS With OFDM Under Per-Antenna Power Constraint - Yu, Xiangbin; Xu, Weiye; Leung, Shu-Hung; Dang, Xiaoyu; Teng, Tao (IEEE transactions on vehicular technology, 2018)
In this paper, three power allocation (PA) schemes for distributed antenna (DA) systems with orthogonal frequency division multiplexing over multipath fading channels are presented. Unlike the conventional total power constraint, power constraints for individual antenna ports are considered. By maximizing the channel capacity of the system subject to per-antenna maximum power constraints, the optimization problem for the PA design is formulated. Based on the block coordinate descent method, an optimal PA scheme to the optimization problem is derived. Considering that the optimal scheme is an iterative algorithm, a suboptimal PA scheme is derived by maximizing an upper bound of the channel capacity, which provides a closed-form PA procedure. Interestingly, this suboptimal scheme can obtain almost the same performance as the optimal one for large number of subcarriers, low maximum power, and/or small number of DA ports. To reduce the performance loss, a modified suboptimal scheme with closed-form PA is developed, and it has the capacity performance very close to the optimal scheme. Computer simulations verify the effectiveness of the three proposed schemes.